Administrator Turnover: The Roles of District Support, Safety, Anxiety, and Violence from Students - Andrew H. Perry; Linda A. Reddy; Andrew Martinez; Susan D. McMahon; Eric M. Anderman; Ron A. Astor; Dorothy L. Espelage; Frank C. Worrell; Taylor Swenski; Kailyn Bare; Christopher M. Dudek; Jared Hunt; et al. (Behavioral Sciences)
Researchers have examined the importance of school administrative support for teacher safety, victimization, anxiety, and retention; however, studies to date have rarely focused on school administrators’ perceptions of support by their district leaders, and its relation to administrators’ anxiety/stress, safety, and their intentions to transfer or quit their jobs. In the current study of 457 PreK-12th grade school administrators in the United States, structural equation modeling was used to examine relations between administrators’ perceptions of support from their district leaders and their anxiety/stress, safety, and intentions to transfer or quit their jobs. Administrator experiences of violence by student offenders served as a moderator. Results indicated that administrators’ perceptions of district leaders’ support were associated with lower intentions to transfer or quit their positions both directly and indirectly as a function of decreased anxiety/stress. District support was positively related to administrator safety, particularly for administrators who reported experiencing more student violence. Findings highlight the importance of district support of administrators for reducing mental health concerns and transfer/quit intentions in the context of student violence against school administrators. Implications of findings for research and practice are presented.